Examining the relationship between parasocial interaction, religiosity, and social media use among followers of Islamic reality shows in Malaysia (ID: RIGS16-188-0352) - Tengku Mohd Azzman, Tengku Siti Aisha; A.Manaf, Aini Maznina (2019)
This research project aims to examine how social media use influence attitude and perceptions towards viewing of Islamic reality shows in Malaysia among university students who regularly use social media, such as Twitter and Facebook. Specifically, this study will focus on social media users’ identification with reality television personalities featured on these shows (coined as ‘parasocial interaction’), and how their perception would influence adoption and use of social media related to these shows. Based on the uses and gratification theory, and literature on parasocial interaction, heavy users of TV programs may experience emotional feelings with characters seen on these shows. Therefore, we propose that social media users who closely identify with characters seen on their favorite Islamic reality show will also be more likely to follow these characters on social media and would be more motivated to use social media in order to interact with these characters or other fans, in order to discuss elements related to the television show. It is also proposed that other individual differences, such as level of religiosity may also mediate the relationship between parasocial interaction and Twitter use regarding the show. The implications of these findings on the role of parasocial interaction, impact of individual differences on media use, and the influence of social media use on television viewing will be discussed in this study.